Spatio‑temporal variations in physicochemical water quality parameters of Lake Bunyonyi, Southwestern Uganda - Saturday,Alex; Lyimo,Thomas J.; Machiwa, John; Pamba,Siajali (SN Applied Sciences, 2023)
The current study was carried out to examine the spatial and temporal variations of physicochemical water quality parameters of Lake Bunyonyi. The observations were made on the surface water of Lake Bunyonyi for 1 year to deter mine the water quality. The basic 12 variables used to determine the quality of water were measured monthly at nine stations. Water temperature, dissolved oxygen (DO), turbidity, electric conductivity (EC), pH and Secchi depth (SD) were measured in the feld, while parameters like total nitrogen (TN), total phosphorus (TP), nitrite-nitrogen (NO2-N), nitrate nitrogen (NO3-N), soluble reactive phosphorus (SRP) were determined following APHA 2017 standard guidelines for physicochemical analysis. Taking into account standard guidelines for drinking water by the Uganda National Bureau of Standards (UNBS) and the World Health Organization (WHO), the water quality index (WQI) was used to determine the water quality. Temperature, DO, pH, turbidity and EC did not difer signifcantly among the study stations (p>0.05) but showed signifcant temporal variations among the study months (p<0.05). Likewise, TN, TP, NO2-N, NO3-N and SRP did not difer signifcantly among the study stations (p>0.05) but showed signifcant temporal variations among the study months (p<0.05). The WQI values ranged from 28.36 to 49 across and from 28.2 to 56.2 between study months with an overall mean value of 36.9. The measured water quality variables did not exceed the UNBS and WHO standards for drinking water in all months and at all stations. According to these values, the water quality of Lake Bunyonyi gener ally belongs to the ‘good’ class in terms of drinking water quality based on the WQI classifcation. The study fndings are fundamentally important for policy makers in setting guidelines for efective lake management.